Safety of sodium-glucose transporter 2 (SGLT-2) inhibitors in patients with type 2 diabetes: a meta-analysis of cohort studies - Li, Chun Xing; Liu, Tian Tian; Zhang, Qian; Xie, Qing; Geng, Xu Hua; Man, Chun Xia; Li, Jia Yi; Mao, Xin Ying; Qiao, Yue; Liu, Hua (Frontiers in Pharmacology, 2023)
Aims: This study aimed to investigate the association between the use of sodium-glucose transporter 2 inhibitors (SGLT-2i) and the risk of diabetic ketoacidosis (DKA), lower limb amputation (LLA), urinary tract infections (UTI), genital tract infections (GTI), bone fracture, and hypoglycemia in cohort studies. Methods: A systematic search was conducted in the PubMed and Embase databases to identify cohort studies comparing the safety of SGLT-2i versus other glucose-lowering drugs (oGLD) in patients with type 2 diabetes mellitus (T2DM). The quality of the studies was assessed using the Newcastle-Ottawa Scale. Primary endpoints were DKA and LLA, while secondary endpoints included UTI, GTI, bone fracture, and hypoglycemia. Hazard ratios (HR) with 95% confidence intervals (CI) were calculated. Results: A total of 9,911,454 patients from 40 cohort studies were included in the analysis. SGLT-2i use was associated with a higher risk of DKA (HR: 1.21, 95% CI: 1.07–1.38, p = 0.003) and GTI (HR: 2.72, 95% CI: 2.48–2.98, p < 0.01). However, it was not associated with an increased risk of LLA (HR: 1.06, 95% CI: 0.92–1.23, p = 0.42), UTI (HR: 0.99, 95% CI: 0.89–1.10, p = 0.83), or bone fracture (HR: 0.99, 95% CI: 0.94–1.04, p = 0.66). Furthermore, SGLT-2i was associated with a reduced risk of hypoglycemia. Furthermore, compared to dipeptidyl peptidase 4 inhibitors, SGLT-2i as a class and individually was associated with an increased risk of DKA. Canagliflozin specifically increased the risk of LLA (HR: 1.19, 95% CI: 1.04–1.36, p = 0.01). The subgroup analysis suggested that SGLT-2i increased the risk of LLA among patients with a history of cardiovascular disease. Conclusion: SGLT-2i versus oGLD was associated with a similar occurrence of LLA, UTI, and bone fracture. However, SGLT-2i was associated with a higher risk of DKA and GTI than oGLD. These findings provide valuable information on the safety profile of SGLT-2i in patients with T2DM and can help inform clinical decision-making.